Rodent models of Parkinson's disease: beyond the motor symptomatology - Campos, Filipa L.; Carvalho, Miguel M.; Cristovão, Ana C.; Je, Goun; Baltazar, Graça; Salgado, António J.; Kim, Yoon-Seong; Sousa, Nuno (Frontiers in Behavioral Neuroscience, 2013)
Parkinson's disease (PD) is classically characterized by motor symptoms; however, non-motor manifestations are increasingly recognized as relevant in this condition. Given the influence of these non-motor symptoms in the well-being of PD patients, it is of major interest to assess these features in studies using PD animal models. Therefore, the present study aims to compare the motor, emotional and cognitive behaviour of three animal models of PD: i) the 6-hydroxydopamine (6-OHDA) lesion model; ii) the paraquat (PQ) induced model and iii) a genetic model based on α-synuclein overexpression (α-syn). 6-OHDA and α-syn vector were injected bilaterally in the substantia nigra of adult male Wistar rats; as for PQ delivery, micro-osmotic pumps were implanted in the interscapular region. Motor deficits were observed in all models. In addition to the motor impairments, the animals of α-syn model presented also a reduction of exploratory activity. Animals exposed to 6-OHDA and PQ displayed a significant increase in both anxiety and depressive-like behavior. Interestingly, only in the 6-OHDA model there was an impairment in working memory performance. Overall, these PD models are suitable for mimicking the motor symptoms associated to PD, and some of them encompass other relevant components of the disorder.